Exercise Improves the Coordination of the Mitochondrial Unfolded Protein Response and Mitophagy in Aging Skeletal Muscle - Yan Wang; Jialin Li; Ziyi Zhang; Runzi Wang; Hai Bo; Yong Zhang (Life, 2023)
The mitochondrial unfolded protein response (UPRmt) and mitophagy are two mitochondrial quality control (MQC) systems that work at the molecular and organelle levels, respectively, to maintain mitochondrial homeostasis. Under stress conditions, these two processes are simultaneously activated and compensate for each other when one process is insufficient, indicating mechanistic coordination between the UPRmt and mitophagy that is likely controlled by common upstream signals. This review focuses on the molecular signals regulating this coordination and presents evidence showing that this coordination mechanism is impaired during aging and promoted by exercise. Furthermore, the bidirectional regulation of reactive oxygen species (ROS) and AMPK in modulating this mechanism is discussed. The hierarchical surveillance network of MQC can be targeted by exercise-derived ROS to attenuate aging, which offers a molecular basis for potential therapeutic interventions for sarcopenia.